A case of putty kidney without pulmonary tuberculosis. (31st May 2013) - Nishant, Kumar; Sharma, Barun Kumar; Philipraj, S Joseph; Singh, Varun Kumar
Abstract : A 30-year-old woman presented with a 1-year history of a dull ache in her left flank along with recent onset of hypertension. There was no history suggestive of tuberculosis and examination was unremarkable. X-ray showed dense opacity in left renal area. Contrast-enhanced CT revealed a non-enhancing and non-excretory left kidney suggesting autonephrectomy. When a 6 week course of antituberculous therapy (ATT) failed to alleviate her symptoms, surgical nephroureterectomy was performed which resulted in complete resolution of symptoms and well-controlled blood pressure without any medication.